Similaridade energética de polimorfos: N-azol-2-fenoxiacetamidas e outros compostos orgânicos. Aditividade energética de interações intermoleculares: carboxilatos de amônio - Rosa, Jéssica Maria Luis (2024)
This thesis presents the studies carried out for (i) self-association and polymorphism of N-(heterocycle)-2-phenoxyacetamide compounds through the identification of intra- and intermolecular interactions; (ii) proposal of a supramolecular energy similarity index (ESIM) to compare relative differences in supramolecular stabilization energy in polymorphic systems of organic compounds and (iii) quantification of intermolecular interactions in ammonium carboxylate salts, evaluating supramolecular energetic stability. The results were organized into three chapters, each addressing one of the themes mentioned. The self-association of a series of N- (heterocycle)amides was evaluated to determine the molecular and supramolecular energetic differences between their polymorph pairs. Based on proposals for crystallization mechanisms, the formation of dimers with the same patterns of intermolecular hydrogen interactions NH··∙N between the amide group and the heterocycle was observed, and changes in nucleation occurred from the second stage of crystallization. The comparison between the molecular and supramolecular stabilization energies for polymorph pairs suggests that intermolecular interactions can compensate for an energetically less stable molecular conformation. The supramolecular stabilization energy of several polymorphic pairs of organic compounds was analyzed and compared. It was observed that evaluating the similarity of the supramolecular stabilization energy in terms of absolute values does not appear to be an adequate approach. From this, a similarity index (ESIM) was developed, which consists of the energetic values normalization of supramolecular clusters of polymorphs, which can be applied to any pair of polymorphic crystalline structures. In the study involving crystalline structures of ammonium carboxylates, the ammonium cation (NH4 + ) was fixed to evaluate the impact of variations in the alkyl chain of selected mono- and dicarboxylate compounds, such as length or degree of unsaturation. Dimers with almost zero intermolecular interaction energies were detected in crystalline structures of ammonium carboxylates, resulting from repulsive interactions with a magnitude similar to that of attractive interactions. Destabilizing interactions occur when portions with the same type of charge come closer together. However, most crystal lattices have energetic characteristics close to those of uncharged organic compounds.